Results and Impacts of the Integrated Land and Water Management for Adaptation to Climate Variability and Change (ILWAC) Project: Evaluation Report - Kizito, Fred; Mwongera, Caroline; Pondi, Brian; Mwungu, Chris M.; Odhiambo, Collins; Koech, Nicholas; Shikuku, Kelvin Mashisia; Nkonya, Ephraim M.; Nigussie, Likie; Appoh, Richard K.; Touré, Abdoulaye; Sakana, Naomi; et al. (International Center for Tropical Agriculture, 2019)
The objective of the evaluation was to assess the results and impacts of the activities of all ILWAC Trust Fundfinanced projects in West Africa using a selected subset, to identify key lessons learned, and to document best climatesmart practices for scaling up. The study entailed participatory evaluation of the results and impacts of various interventions geared towards integrated water resources management for climate change and variability preparedness in West Africa. In this respect, the study identified key lessons learned and documented best climate-resilient practices for scaling up and dissemination to multiple stakeholders in the West African region. 1. Agriculture remains the backbone for sustaining livelihoods in West Africa but faces numerous challenges. Agriculture is an important source of income, food and raw materials in West Africa, employing more than half of the region’s population, which culminated in the adoption of the Comprehensive Africa Agriculture Development Programme (CAADP) in 2003. Few countries, however, have managed to mobilize their agriculture sector to deliver on development outcomes such as food and nutrition security, poverty reduction, economic growth, job creation, youth employment and industrialization. Agriculture is vulnerable to climate change, resulting from sensitivity and exposure to climate shocks and lack of capacity to cope with and adapt to such changes. ILWAC evaluation study results from household surveys, focus group discussions and key informant interviews indicate that agricultural productivity in the region remains low, lagging far behind other regions of the world. Contributors to such low productivity include incidence of climate risks (drought, floods and high temperatures), pests and diseases, low technology adoption, limited access to financial services, limited access to markets and market information and limited access to good road networks (Plate 1). All the aforementioned contributors are valid denominators for all the seven ILWAC project areas that were evaluated. 2. Farmers in West Africa are particularly vulnerable to climatic shocks because of their high dependence on rainfed agriculture for their livelihoods. There is an evident lack of access to formal safety nets as indicated by farmers in Senegal (ENRACCA-WA) and Burkina Faso (AmREACCAF and APESS) projects. Climate change has already exerted significant impacts in the region. Since the 1970s, the region has experienced the occurrence of many droughts. Temperatures have increased in the second half of the 20th Century, especially in the latter 20 years of the same period. Farmers reported drought (about 40% of treatment and control groups), as the most prevalent climatic shock experienced over the last five years, followed by erratic rainfall, floods and invasion of crop pests and locusts. We identified eleven coping strategies, out of which three strategies were categorized based on a gradient of severity of food insecurity into low, moderate, and high food insecurity. During low food insecurity, households employ food-maximizing strategies such as purchasing food and eating less food and involving a low commitment of domestic resources that all enable quick recovery of households once the crisis eases. In times of moderate food insecurity, a greater commitment of household resources is increasingly required to meet subsistence needs. Coping strategies developed by households include sale of food reserves, use of savings, sale of livestock, borrowing food, and borrowing money (from friends, relatives, private lenders and banks). During high food insecurity, strategies are a sign of failure to cope with the food crisis and may involve drastic options that may undermine their future ability to prevent, mitigate, cope, and recover from shocks. Households adopt sale of assets such as land and homes, keeping children home from school, food aid and migration. The use of irrigation and rainfall water harvesting for agriculture remain low, despite prevalent droughts and widespread rainfed agricultural practices. One of the reasons is that most farming communities are far from rivers: hence considerable investment is required to develop irrigation in many project areas. 3. Although farmers use various strategies highlighted above, they will need support to double their efforts with innovative climate- smart agricultural practices and technologies to remain food secure. Areas where ILWAC interventions were targeted showed positive results, but broader efforts to scale out the successes are needed to achieve a greater impact. Overall, the ILWAC project beneficiaries reported higher adoption rates of climate-smart practices, demonstrating a favourable impact of the project. However, low awareness of the most appropriate technologies to cope with climate shocks was reported across all study areas yet, the region is expected to experience increasing climatic shocks with total precipitation predicted to increase for the most part more notably between July and October by 2050. Increases in precipitation are predicted to cause crop damages and floods. Overall, temperatures will rise by about 2°C to 3°C over the same time period. Higher temperatures of 3°C to 6°C are projected for the end of the 21st century (Niang et al., 2014). Despite these impending changes, few farmers have adjusted their farming strategies in response to climate risks, owing to limited knowledge on appropriate adaptation options and low endowment with production resources. As a result, ILWAC interventions were targeted to reverse these challenges. Their successful implementation showed positive results, which are largely limited to specific areas of implementation. Therefore, broader scaling out ILWAC interventions provided success stories tailored to specific contexts (biophysical and socio- economic); hence offered lessons and opportunities for replicating the bright spots with a regional approach. Across the seven projects, evaluation results indicated a couple of selected successes in the region (Plate 1). Selected successes make up potential candidates for scaling up climate-smart agricultural technologies and practices, and innovative approaches notably, including: i. Innovation platforms as a pillar for change: The successful establishment of innovation platforms across all project countries was evident but have remained largely underdeveloped and not utilized to their full potential. Platforms provided a framework for sharing knowledge on adaptation innovations to climate change, providing a good entry point for technology dissemination in target areas across all project countries. The study showed that the innovation platform model can offer the potential to organize stakeholders to address the objective of improving the livelihood of their members. IPs, however, need a strong voice to demand the needed services from service providers, negotiate and advocate for collective interests with the private sector and government. The use of a participatory development communication (PDC) within IPs would greatly increase their sustainability; ii. Increased human and institutional capacity for stakeholders: The enhancement of capacity for diverse stakeholder groups, including farmers, players in all segments of priority value chains, extension agents, policymakers and researchers (All project countries) resulted in significant positive results such as increased capacity towards awareness of CSA technologies and application of appropriate adaptation measures in their communities. This highlights the need to prioritize linkages amongst farmer organizations, extension and agricultural research; iii. Integrated landscape approaches for natural resources management provided exponential benefits: The pioneering of integrated land and water management for adaptation to climate variability and change improved management of natural resources in specific target countries, for example, in Burkina Faso, the relative reduction in sedimentation by up to 70%; and that in reduced runoff by up to 30% which helped improve the farmers’ agricultural practices and livelihoods (AmREACCAF-Burkina Faso). This also increased storage of water in the Boura reservoir through avoided sedimentation. Beyond water provision for household use, these reservoirs serve as key food baskets for fisheries and irrigation for households; iv. Integrated and diversified options offered opportunities to increase resilience and unlock the potential for rural smallholder livelihoods: The ILWAC project improved implementation of innovative agronomic interventions that substantially reduced the yield gap for millet for example the use of improved crop varieties (drought tolerant and early maturing) resulted in a 10 fold yield increase in grain biomass (ENRACCASenegal). Additional strategies include soil amendments in the form of organic and inorganic fertilizer sources, weed control practices as well as improved storage techniques (ISFM-Benin); Household enterprise diversification with agroforestry tree species enhanced the resilience of smallholder communities with climatesmart benefits such as windbreaks, these modified the micro-climate of the area that enhanced food security and revenue generation within target communities, increased farmer adaptive capacity and overall soil health attributes (ENRACCA- Senegal). 5. Women empowerment resulted in improved rural livelihoods: Improved gender dynamics regarding the roles, activities and representativeness within the selected projects had a positive impact on women empowerment for all project countries. There are numerous ways by which women were empowered e.g. conducting off-season vegetable cultivation allowed women to fetch increased returns (3 times than the normal price) in the off-season months. There were efforts to promote increased participation of women in the projects, offering opportunities to freely express themselves, highlight their needs and specific experiences. However, participation of women in leadership positions was generally low (less than 10%). In addition, women were able to benefit from the capacity building provided by the project, and access technologies and inputs resulting in higher production and subsequent incomes than before. Male-headed households were more likely to practice more CSA technologies by a factor of about 1 compared to female headed households. There was evidence of better access to financial services and training through village savings and loan associations, and gender empowerment. A key attribute of the assessed projects was that for the most part, women farmers were not well organized into interest groups with the capacity to promote their interests and engage in advocacy activities geared at influencing policy for their ultimate benefit. This was a missed opportunity especially in the context of existing innovation platforms that needs concerted efforts and strengthening. 6. More economic and social safety nets for smallholder livelihoods beyond ILWAC beneficiaries are needed: ILWAC enhanced farmers’ access to climate-resilient and low-emission practices and technologies, including crop, livestock, soil and water management options and energy saving technologies. ILWAC increased the number of CSA practices implemented by three practices more compared to non-participation. Results further showed that education level is associated with higher income. Higher value assets such as livestock did also significantly influenced income. ILWAC increased significantly the value of assets to almost 90%; a factor attributable to additional assets that were distributed to farmer groups such as the case of Gambia, Senegal and Sierra Leone. This study therefore confirms that more assets in ILWAC supported households offered better livelihood options than those in the control group. Results further show that male-headed households have a higher value of assets than female-headed households. On the overall, although participation in ILWAC increased income by 19%, there remains room for further improvement amongst the ILWAC beneficiaries given the lower differences in the economic domain for sustainable intensification exemplified before and after the ILWAC project on Plate 2. Likewise, Plate 2 highlights that better options are needed in the social domain to ensure that ILWAC beneficiaries can significantly gain from social dividends (e.g. strengthened farmer groups, collective action, and shared labor). Given the highlighted successes among the ILWAC beneficiaries, efforts will be needed to scale these bright spots beyond the ILWAC beneficiaries to wider geographical coverages. 7. There is need for concerted efforts towards supporting technical, financial, institutional and governance needs within the target countries in order to make community livelihoods more resilient to climate change. Despite the recorded successes there remains room for improvement in several institutional and governance realms. Farmers in the project sites are faced by poor extension, with the ratio of government paid extension officers to that of farmers being low, only 33% of the households have access to extension service. This has a negative impact on the quality of extension services being offered and building adaptive capacity to deal with climate change. A significant challenge remains in all project countries to get the technologies widely used due to the lack of a suitable enabling environment among others — extension services, financial resources, infrastructure, risk management and cross-sectoral linkages. Farmers are further constrained by having limited access to climatic information. Effective research and innovation are also needed to continuously improve practices and technologies. This calls for a policy recommendation where concerted efforts are needed to mobilize financial resources and build the capacity of West African researchers, policy-makers and institutions to understand, carry out and use good quality data towards informed decision making and scenario analyses (Also see evidence revealed by Plate 2).Enabling policy and institutional environment can provide the conditions and incentives for scaling out.